Social/Affective Learning Strategies Used By English Department Student of UMS in Developing English Speaking Skill - Yuniatun., Ika (2012)
The objective of the research is to describe the types of social/affective learning strategies used by students of English Departement UMS in speaking II class. This is a qualitative research. The research is a case study of social/affective learning strategy in speaking ability of students of UMS. The subject of the research is three students of English Department Muhammadiyah University of Surakarta namely S1, S2, and S3 based on their ability in Speaking skill. The methods of collecting data are observation and interview. To analyze the data the writer applied critic analytic technique. The result of this research shows that social/affective learning strategies play a significant role in speaking. Social learning strategy which most frequently used is asking for clarification, asking for correction, and cooperating with others. Social learning strategy gives directly contribution to the students who have a middle or poor ability in speaking skill to overcome their misunderstanding with lecturer's explanation because the lecturer is a native speaker. Affective learning strategy which most frequently used is using laughter, deep breathing, and discussing with others. In addition, the students can reduce their anxiety in speaking class using affective learning strategy which leads them to speak fluently while they get a topic from the lecturer especially a native speaker.